Services publics — Pouvoir du tribunal d'arbitrage d'amender sa propre sentence (Relations industrielles / Industrial Relations, 1962)
SummaryA council of arbitration, appointed under the Act respecting Municipal and School Corporations and their Employees, which remained in office after rendering its award with power to hear any dispute arising as to its interpretation but whose authority has been limited by a clause in the agreement annexed to the award and reading as follows:Le Tribunal d'arbitrage n'aura pas juridiction pour rendre une décision incompatible avec les dispositions de cette convention, ni pour changer, modifier ou amender quelque partie que ce soit de cette convention.has the right to interpret its award and to correct a simple clerical error, but not to amend it.In the present instance, under the terms of the award, the employees of the same category as plaintiff were entitled to be paid at the rate of $1.29 per hour for time worked up to 44 hours a week, plus 50% for time worked in excess of 44 hours a week, the whole retroactive to a specified date. It cannot be said that it is only through a clerical error that the award was made retroactive not only as to the rate of pay but also as to the hours of work a week, even if it resulted in hardship for the employer. A tribunal cannot amend its decision any time that it finds that it acted without full information or complete realization of the effect of such dicisionAn arbitration award is not null because it was made retroactive for 13 months, contrary to the article 12 of the above-mentionned Act which limits the retroactivity to 12 months; but tis retroactivity should be reduced to that period. In amending its award as it did the council acted without jurisdiction and plaintiff was justified in taking action for the amount due to him under the award as originally made, but with the period of retroactivity shortened from 13 to 12 months.